Pengetahuan, sikap, dan tindakan dalam implementasi SDGs umat Buddha di Provinsi Papua Barat - Sugiarto Sugiarto; Hendri Hendri; Jacob Manusawai (Cassowary, 2023)
ABSTRACT: The 2030 Agenda for Sustainable Development Goals is to end poverty, reduce inequality and protect the environment. The purpose of this study was to determine the level of knowledge, attitudes and action of Buddhists towards the Sustainable Development Goals based on the characteristics of the regencies in the province of West Papua. Respondents consisted of Buddhist figures and people in Sorong City, Sorong Regency, Manokwari Regency, Fakfak Regency and Teluk Bintuni Regency in West Papua Province. Data analysis using a Likert scale which is divided into 5 categories The results showed that the knowledge, attitude and action with a range of categories from good to very good with each value of from the highest in Sorong City (84%) followed by Manokwari Regency (82%), Teluk Bintuni Regency (80%), Fakfak Regency (76%) and Sorong Regency (55 %), respectively. Education is the biggest factor on the level of knowledge, attitudes and actions. The higher the level of education, the better the level of social life and the more advanced the culture of a region has an effect on the high knowledge, attitudes and actions in implementing the SDGs of Buddhists in West Papua Province.